Examining Leadership-Induced Psychosocial Hazards: A Qualitative Case Study on the Impacts among Academics - Khalid, Haniza Abdul; Isha, Ahmad Shahrul Nizam; Naji, Gehad Mohammed Ahmed; Puteh, Marlia; Al-Mekhlafi, Al-Baraa Abdulrahman (Journal of Ecohumanism, 2025)
Leadership profoundly influences the well-being of employees across various domains, including their physical, emotional, and psychological states. This qualitative inquiry delves into the interplay between leadership styles and psychosocial hazards within private research-focused universities. This study extracts nuanced insights into the leadership dynamics prevalent in their academic environments through standardised open-ended interviews with seventeen academics. Utilising the Atlas.ti software for analysis, thematic examination revealed eight distinct codes characterising detrimental leadership typologies: self-serving, control-oriented, unempathetic, biased & favoritist, narcissistic, authoritarian, misleading, and weak & indecisive leaders. These findings illuminate the profound psychological and social repercussions of such leadership styles within academia, emphasising the imperative for institutional safeguards to mitigate their adverse effects. The study enriches the ongoing discourse on leadership in higher education and advocates for a critical reevaluation of leadership practices to cultivate a more supportive and productive academic milieu.